Diagnóstico ambiental integrado e subsídios ao estabelecimento de metas de qualidade da água na Bacia Hidrográfica do Rio Jaboatão (PE) - Souza, Antonio Donizetti Gonçalves de (Universidade Federal de São Carlos, 2002)
The main subject of the present work was to realize integrate environmental study in the Jaboatão River, a densely urbanized and industrialized basin, and to offer subsidies to the establishment of water quality goals. Eight sampling points were established and was sampling monthly during period from September/97 to February/99. The following variables were analyzed: temperature, pH, turbidity, conductivity, chlorine, alkalinity, dissolved oxygen, biochemical oxygen demand, fecal coliforms, nitrate, total phosphorus, total solids, Ca, Mg, Na, K and Fe. The sediments were collected at four sites being analyzed the metals Cd, Pb, Cu, Cr, Fe, Mn, Ni and Zn. Water quality historical data (1986-1996) were also recovered and analyzed. The following thematic maps were produced: land uses, legal protection, hydrography, municipal limits, geology, soils, water withdrawals and industrial sources of pollution. Based on maps of the legal protection areas, water withdrawals and industries, regions with water uses restrictions were delimited. Within these regions groups of water bodies were established using guidelines for protection and recovery and proposing water quality classes based on CONAMA resolution 20/86. The results demonstrate a condition of environmental degradation as attested to by several water quality variables analyzed. In the stations representing urbanized areas, the worst water quality conditions were found, especially in the summer period, resulting from industrial and domestic effluents. The critical variables were dissolved oxygen, fecal coliformes, and total phosphorus, placed the area within class 3 and 4 according CONAMA resolution 20/86. Water use regulation was proposed as a useful tool in beginning discussing of water quality goals according classification system proposed by the CONAMA resolution 20/86. The approach presented in this study can be used as a subsidy by public agencies, stakeholders and citizens responsible for establishing guidelines and effective measures for watershed protection and recovery.
Integrated environmental diagnosis and support for the establishment of water quality goals in the watershed Jaboatão River (PE)
Keywords: Bacias hidrográficas; Gerenciamento ambiental; Qualidade de água; Planejamento ambiental; Gestão ambiental; Instrumentos de gestão ambiental; Watersheds; Environmental management; Water quality; Environmental planning; Environmental management; Environmental management instruments; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA